Potato (Solanum tuberosum L.) Cultivars Interact with Wound Healing Period to Modulate Sprout Emergence, Crop Stand, and Productivity - Connor L. Buckley; Keegan B. Lloyd; Mohan G. N. Kumar; Jacob M. Blauer (Plants, 2025)
The effects of wound healing on crop stand and productivity were examined on the potato (Solanum tuberosum L.) cultivars Alturas (Alt), Russet Burbank (RB), and Clearwater Russet (CW). Tuber yields increased linearly with an advancing wound healing period irrespective of the cultivar (R2 = 0.91). In contrast to unhealed controls, RB and CW wound-healed for 8 days produced a 6% and 8% greater yield, respectively, while a shorter wound healing period of 2 days increased Alt yield by 7%. Increases in tuber yield, a consequence of enhanced specific tuber weight across wound healing periods, contributed towards increased relative crop value in Alt (13%), RB (22%), and CW (19%). In further lab evaluations, Alt exhibited increased desiccation resistance and was associated with an earlier induction (24 h post-wounding) of feruloyl transferase (FHT) compared to CW and RB. Since FHT facilitates suberin and wax development, delayed FHT induction likely promoted fresh-weight loss in CW and RB compared to Alt. Enzymatic evaluations to assess the production of reactive oxygen species to protect fresh-cut seed found that RB had the highest activities of superoxide dismutase and peroxidase. This study demonstrates the broad benefits of planting wound-healed seed while highlighting opportunities to improve best practices and genetic improvement for wound healing response.